2022
DOI: 10.1186/s13102-022-00519-w
|View full text |Cite
|
Sign up to set email alerts
|

The impact of resistance exercise range of motion on the magnitude of upper-body post-activation performance enhancement

Abstract: Background Various studies have used different exercise protocols as post-activation performance enhancement (PAPE) stimulus; however, little attention has been given to the effects of exercise range of motion on the PAPE effect and subsequent performance enhancement. This study aimed to compare the PAPE responses induced by the bench press performed with different ranges of motion on subsequent bench press throw performance. Methods Ten resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 46 publications
1
25
0
Order By: Relevance
“…Nevertheless, the COD test used in this study consists mainly of lateral movements; thus, the UNI-CA used could not reflect the involvement of the same muscle groups. The importance of exercise similarity has been pointed out in previous studies ( Dello Iacono et al, 2016 ; Krzysztofik et al, 2022 ). For example, Krzysztofik et al (2022) showed that the CA and subsequent explosive task should be as similar as possible regarding the range of motion to maximize the PAPE effect.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…Nevertheless, the COD test used in this study consists mainly of lateral movements; thus, the UNI-CA used could not reflect the involvement of the same muscle groups. The importance of exercise similarity has been pointed out in previous studies ( Dello Iacono et al, 2016 ; Krzysztofik et al, 2022 ). For example, Krzysztofik et al (2022) showed that the CA and subsequent explosive task should be as similar as possible regarding the range of motion to maximize the PAPE effect.…”
Section: Discussionmentioning
confidence: 64%
“…The importance of exercise similarity has been pointed out in previous studies (Dello Iacono et al, 2016;Krzysztofik et al, 2022). For example, Krzysztofik et al (2022) showed that the CA and subsequent explosive task should be as similar as possible regarding the range of motion to maximize the PAPE effect.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The redistribution of bioelectrical activity of HM depending upon rotation of the lower leg, which we revealed, will optimize components for carrying out muscular-fascial testing. This will also make it possible to qualitatively regulate conditions of a local physical effect on the area of contraction in functional imbalance [30,31].…”
Section: Discussionmentioning
confidence: 99%